Acute heart failure after non-cardiac surgery: incidence, phenotypes, determinants and outcomes. (3rd October 2022) - Gualandro, D M; Puelacher, C; Chew, M S; Andersson, H; Lurati Buse, G; Glarner, N; Mueller, D; Cardozo, F A M; Burri, K; Mork, C; Wussler, D; Bolliger, D; et al.
Abstract: Background: Primary acute heart failure (AHF) is an established and common cause of hospitalization. AHF may also develop secondarily, e.g. postoperatively (pAHF). Little is known about pAHF. Purpose: To assess the incidence, phenotypes, determinants and outcomes of pAHF following non-cardiac surgery. Methods: We prospectively included 9, 164 consecutive patients at high cardiovascular risk undergoing 11, 262 non-cardiac surgeries. The incidence, phenotypes, determinants and outcome of pAHF, centrally adjudicated by independent cardiologists, was determined. Logistic regression models identified the risk factors for pAHF. Cox regression analysis compared mortality and AHF readmission within 1 year in patients with and without pAHF. External validation was performed using a prospective cohort multicenter study of 1250 patients. Results: The incidence of pAHF was 2.5% (95% confidence interval [CI] 2.2–2.8%). pAHF most often occurred on postoperative day 2 (median day 4). About half of pAHF (51%) occurred in patients without known HF (de novo pAHF), and 49% in patients with chronic HF. Preserved left ventricular ejection fraction (LVEF) was the dominant phenotype among de novo pAHF (72%), while reduced LVEF was dominant among pAHF in chronic HF (43%). Age, coronary artery disease, peripheral artery disease, diabetes, urgent/emergent surgery, chronic HF, atrial fibrillation, chronic obstructive pulmonary disease, anemia, and chronic myocardial injury were independent predictors of pAHF. Patients with pAHF had significantly higher all-cause mortality (44% vs. 11%, p<0.001) and AHF readmission (15% vs. 2%, p<0.001) within 1 year than patients without pAHF. pAHF was an independent predictor of all-cause mortality (adjusted hazard ratio [aHR] 1.7 [95% CI 1.3–2.2]; P<0.001) and AHF readmission (aHR 2.7 [95% CI 1.7–4.2]; P<0.001) within 1 year. Findings were confirmed in an external validation cohort of 1250 patients, e.g. incidence of pAHF 2.4% (95% CI, 1.6–3.3%). Conclusions: pAHF frequent developed following non-cardiac surgery, being de novo in about half of cases, and associated with an unacceptable high mortality. Strategies focusing on early detection and treatment of pAHF seem warranted. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSwiss Heart Foundation